Adenoid and tonsil surgeries in children: How relevant is pre-operative blood grouping and cross-matching? - Lucky Onotai; Opubo da Lilly-Tariah (Wolters Kluwer Medknow Publications, 2013)
Background: As a part of pre-operative evaluation, several otolaryngologists group and cross-match blood routinely for children undergoing adenoid and tonsil surgeries. This practice has generated several debates either in support or against this practice. The aim of this study is to critically evaluate the incidence of post-tonsillectomy (with or without adenoidectomy) bleeding and blood transfusions in otherwise healthy children with adenoid/tonsil pathologies conducted in the University of Port Harcourt Teaching Hospital (UPTH). Patients and Methods: A descriptive retrospective study of children who underwent adenoid and tonsil surgeries in the Department of Ear, Nose and Throat (ENT) surgery of UPTH from January 2003 to December 2012. Children with family history of bleeding disorders and derangement of clotting profile as well as different co-morbidity like sickle cell disease were excluded from this study. The patients' data were retrieved from the registers of ENT out-patient clinics, theatre registers and patients case notes. Demographic data, indications for surgery, preoperative investigations, complications and management outcomes were recorded and analyzed. Results: Out of 145 children that had adenoid and tonsil surgeries; only 100 met the criteria for this study. The study subjects included 65 males and 35 females (male: female ratio 1.9:1) belonging to 0-16 years age group (mean age: 3.46 ± 2.82 years). The age group of 3-5 years had the highest (n = 40, 40%) number of surgeries. Adenotonsillectomy was the commonest (n = 85, 85%) surgery performed on patients who had obstructive sleep apnea (OSA). The commonest (n = 6, 6%) complication was haemorrhage, and only few (n = 3, 3%) patients had blood transfusion. However, mortality was recorded in some (n = 3, 3%) patients. Conclusion: This study confirms that the incidence of post adenoidectomy/tonsillectomy bleeding in otherwise healthy children is low and rarely requires blood transfusion. We can conclude that routine preoperative blood grouping and cross-matching of blood for all children undergoing elective adenoid and tonsil surgeries seemed irrelevant and not cost effective. However, it could be carried out in only special circumstances.